Effects of Digital Story-telling on Motivation, Critical Thinking, and Academic Achievement in Secondary School English Learners - Tamimi, Murad A. Ahmed (Research in Social Sciences and Technology, 2024)
While examining the findings, this study concentrated on academic success, critical thinking, and motivation. for demonstration. Secondary school students studying English are involved in digital story-telling research. A quasi-experimental approach was employed in the research with 48 11th grade students who took pretests and posttests. Teaching as DST in the experimental group and teaching as teaching in the control group were the two degrees of CT-integrated instruction that were used. Gather both quantitative and qualitative information, such as responses to academic questions and the outcomes of tests of English language and cognitive skills. Through the addition of unique cultural narratives with a Palestine focus, the work advances the DST tradition. This program sheds information on how learning outcomes for students are impacted by daylight saving time. Because ANCOVA yields effective and objective results, it was utilized in the data analysis process.